Conductive anti-corrosion material

By applying thermodynamic stable, conductive, chemically inert binary or ternary phosphide materials on metal bipolar plates, the dual requirements of corrosion resistance and conductivity in fuel cell environment are solved, and high efficiency under high temperature acid conditions are achieved Corrosion resistance and conductivity.

CN112151823BActive Publication Date: 2024-12-31ROBERT BOSCH GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010596802.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-26
Filing Date
2020-06-28
Publication Date
2024-12-31
Estimated Expiration
2040-06-28

AI Technical Summary

Technical Problem

In fuel cell environment, it is difficult for metal bipolar plate materials to have corrosion resistance and conductivity at the same time. Especially in highly corrosive environments, existing coatings are prone to degradation under high temperature and acidic conditions, resulting in material failure.

Method used

Thermodynamically stable, conductive, chemically inert binary or ternary phosphide materials are used as the surface coating, and the specific form is AxPy or AxBzPy, where A and B are metal elements, x, y, and z are numerical values, and the dopants include N , C or F, corrosion resistance and conductivity formed on the metal substrate.

Benefits of technology

In the presence of HF, at 80°C, pH 2-3, the material exhibits corrosion resistance less than 10µA cm-2 and conductivity greater than 100 S cm-1, ensuring the stability and conductivity of the bipolar plate and reducing the The corrosion risk of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112151823B_ABST
    Figure CN112151823B_ABST
Patent Text Reader

Abstract

The present invention relates to a conductive anti-corrosion material. A proton exchange membrane fuel cell bipolar plate comprises a metal substrate having a body portion and a surface portion, wherein the surface portion comprises an anti-corrosion conductive binary phosphide material having formula (I): x P y (I), wherein A is an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal or a metalloid, x, y are each independently a number selected from 1-15, and the binary phosphide material is configured to impart corrosion resistance and electrical conductivity to the metal substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to thermodynamically stable, electrically conductive, chemically inert binary and / or ternary phosphide materials that are capable of imparting corrosion resistance to substrates in chemically aggressive environments such as fuel cells. Background Art

[0002] Metals have been widely used materials for thousands of years. Various methods have been developed to protect metals and prevent them from corroding or disintegrating into oxides, hydroxides, sulfates and other salts. In some industrial applications, metals are particularly susceptible to corrosion due to aggressive working environments. Non-limiting examples may be metal components of fuel cells and their bipolar plates (BPPs). In addition, certain components such as BPPs not only need to have sufficient chemical inertness to resist degradation in the highly corrosive environment of fuel cells, but also need to be conductive to promote electron transfer in the oxygen reduction reaction of fuel cells. Finding materials that meet these two requirements has become a challenge. Summary of the invention

[0003] According to one embodiment, a proton exchange membrane fuel cell bipolar plate is disclosed. The bipolar plate includes a metal substrate having a body portion and a surface portion, wherein the surface portion includes a corrosion-resistant conductive binary phosphide material having formula (I):

[0004] A x P y (I)

[0005] Wherein A is an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal or a metalloid, x, y are each independently selected from 1-15, and the binary phosphide material is configured to impart corrosion resistance and electrical conductivity to the metal substrate. At about 80°C, pH about 2-3, and the presence of 0.1 ppm HF in the solution, the corrosion resistance of the bipolar plate can be less than about 10 µA cm -2 A may be an element from the fourth or fifth period of the periodic table. A may be a group VIII.B element. The electrical conductivity of the material may be greater than about 100 S cm -1 The surface portion may comprise at least about 50 wt % binary phosphide. The bulk portion may be steel, graphite, aluminum, titanium or copper. The surface portion may further comprise a dopant comprising at least one of N, C or F.

[0006] In an alternative embodiment, a proton exchange membrane fuel cell bipolar plate is disclosed. The bipolar plate comprises a metal substrate having a bulk portion and a surface portion, wherein the surface portion comprises a corrosion-resistant conductive ternary phosphide material having formula (II):

[0007] A x Bz P y (II),

[0008] Wherein A, B are each one of alkali metal, alkaline earth metal, transition metal, post-transition metal or metalloid, x, y, z are each independently selected from 1-15, and the material is configured to impart corrosion resistance and electrical conductivity to the substrate. A and B may both be from Group VIII.B of the periodic table. At least one of A or B may be from the fourth or fifth period of the periodic table. The surface portion may further include a dopant comprising at least one of N, C or F. The interfacial contact resistance between the substrate and the material may be less than about 0.01 ohm cm 2 The electrical conductivity of the material may be greater than about 100 S cm -1 At about 80°C, pH about 2-3, and the presence of 0.1 ppm HF in the solution, the corrosion resistance of the bipolar plate can be less than about 10 µA cm -2 .

[0009] In yet another embodiment, a corrosion-resistant and conductive substrate is disclosed. The substrate may include a bulk portion and a surface portion material, wherein the surface portion material includes a binary phosphide, a ternary phosphide, or both having formula (I), (II):

[0010] A x P y (I) A x B z P y (II)

[0011] A and B are each one of an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal or a metalloid, and x, y, and z are each independently a number selected from 1 to 15. The surface portion material can be configured to impart to the substrate a surface conductivity of less than about 10 µA cm at about 80°C, a pH of about 2-3, and the presence of 0.1 ppm HF in solution. -2 The corrosion resistance is greater than about 100 S cm -1 The surface portion material may comprise both binary and ternary phosphides. A in both the binary and ternary phosphides may be the same element. A and B may both be from group VIII.B of the periodic table. The surface portion material may further comprise a dopant comprising at least one of N, C or F. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 depicts a schematic composition of a proton exchange membrane fuel cell including a bipolar plate according to one or more embodiments; and

[0013] Figure 2 A perspective view of a non-limiting example of a bipolar plate having a body portion and a surface portion comprising a corrosion resistant and electrically conductive material according to one or more embodiments is shown. DETAILED DESCRIPTION

[0014] Embodiments of the present disclosure are described below. However, it should be understood that the disclosed embodiments are only examples, and other embodiments may take various and alternative forms. The drawings do not have to be to scale; some features may be exaggerated or minimized to show the details of a particular component. Therefore, the specific structural and functional details disclosed herein should not be interpreted as restrictive, but merely as a representative basis for teaching those skilled in the art to use the embodiments of the present invention in various ways. As will be understood by those of ordinary skill in the art, the various features shown and described with reference to any one of the figures may be combined with the features shown in one or more other figures to produce embodiments that are not explicitly shown or described. The combination of the features shown provides representative embodiments for typical applications. However, various combinations and modifications of features consistent with the teachings of the present disclosure may be desirable for specific applications or implementations.

[0015] Except where expressly indicated, all numerical quantities expressing dimensions or material properties in this specification are to be understood as being modified by the word "about" in describing the broadest scope of the present disclosure.

[0016] The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein and applies mutatis mutandis to normal grammatical variations of the originally defined abbreviation. Unless expressly stated to the contrary, measurements of properties are determined by the same techniques as previously or later cited for the same property.

[0017] The terms "substantially" or "approximately" may be used herein to describe the disclosed or claimed embodiments. The terms "substantially" or "approximately" may modify a value or relative property disclosed or claimed in the present disclosure. In this case, "substantially" or "approximately" may mean that the value or relative property it modifies is within ±0%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or 10% of the value or relative property.

[0018] Description of a group or class of materials as suitable for a given purpose in connection with one or more embodiments means that mixtures of any two or more members of the group or class are suitable. Descriptions of ingredients in chemical terms refer to the ingredients when added to any combination listed in the specification, and do not necessarily exclude chemical interactions between the ingredients of the mixture once mixed. The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein, and applies mutatis mutandis to normal grammatical variations of the initially defined abbreviation. Unless expressly stated to the contrary, measurements of properties are determined by the same techniques as previously or later cited for the same property.

[0019] Metals are a widely used class of materials in many industries, including automobiles, construction, household appliances, tools, pipes, railroad tracks, coinage, etc. Metals have been used for thousands of years and remain the material of choice for certain applications due to their properties such as strength and resilience. However, for many applications where metals are used, corrosion of the metal is a major source of fatigue and life limitation.

[0020] Corrosion is a natural process that converts refined metals into chemically more stable forms such as oxide(s), hydroxide(s), sulfide(s) and / or other salts of the metal. The conversion is manifested as a gradual destruction of the metallic material caused by electrochemical oxidation of the metal in reaction with an oxidant such as oxygen or sulfate. Corrosion can be caused by exposing the metal substrate to moisture in the air, solutions with a relatively low pH, various chemicals such as acids, microorganisms, elevated temperatures and / or other factors. Especially in acidic environments, corrosion begins at the interface between the bulk metal material (e.g., steel) and the solution (e.g., ions dissolved in water or a surface layer of water that react to degrade the bulk material).

[0021] Many efforts have been made to prevent or slow down the corrosion of metals. For example, various types of coatings have been developed. Example coatings include applied coatings such as paints, platings, enamels; reactive coatings containing corrosion inhibitors such as chromates, phosphates, conductive polymers, surfactant-like chemicals designed to inhibit electrochemical reactions between the environment and the metal substrate, anodized surfaces, or biofilm coatings. Other anti-corrosion methods include controlled permeability templates, cathodic protection, or anodic protection.

[0022] However, the most popular solution to the corrosion problem is still to strengthen the vulnerable metal surface with a coating. Therefore, most corrosion-resistant surfaces include one or more chemically inert coatings or protective layers that can slow down and / or at least partially prevent corrosion from occurring. There remains the challenge of finding a material with substantial corrosion resistance that is also environmentally friendly, economical, and has excellent performance characteristics.

[0023] In addition, some applications are highly susceptible to corrosion due to their environmental factors. The non-limiting example of such an application is a proton exchange membrane fuel cell (PEMFC). PEMFC is an environmentally friendly substitute for the internal combustion engine of a variety of vehicles such as automobiles and buses. PEMFC generally has the characteristics of relatively high efficiency and power density. The very attractive feature of the PEMFC engine is carbon-free emission, provided that hydrogen fuel is obtained in an environmentally friendly manner. Except being a green engine, PEMFC can also be used for other applications such as fixed and portable power sources.

[0024] The working environment of PEMFC itself causes its own corrosion due to various reasons. For example, there is a low voltage between the startup and shutdown of PEMFC, PEMFC has a strong acidic environment, fluoride ions are released from the polymer membrane during PEMFC operation, both H2 and O2 are present at the anode during startup and shutdown, which leads to high cathode potentials that produce cathode corrosion, fuel permeation of hydrogen or oxygen from the anode to the cathode, or vice versa, etc. Therefore, PEMFC requires durable components that can withstand the above conditions.

[0025] Figure 1 A non-limiting example of a PEMFC is depicted in . The core component of the PEMFC 10 that helps produce the electrochemical reactions required to separate electrons is the membrane electrode assembly (MEA) 12. The MEA 12 includes subcomponents such as electrodes, catalysts, and polymer electrolyte membranes. In addition to the MEA 12, the PEMFC 10 typically includes other components such as current collectors 14, (one or more) gas diffusion layers 16, gaskets 18, and (one or more) bipolar plates 20.

[0026] The bipolar plate or BPP 20 is implemented in the PEMFC stack to distribute gases, collect current and separate the individual cells in the stack from each other. The BPP 20 also provides additional functions, such as removing reaction products and water and thermal management within the PEMFC 10. The BPP 20 is also a relatively expensive component and is a common cause of degradation of the PEMFC system. For example, the BPP may constitute about 60-80% of the weight of the stack, about 50% of the stack volume, and about 25-45% of the stack cost. In order to keep costs low, the BPP 20 is typically made of metal, such as steel, such as stainless steel. Alternative materials such as aluminum or titanium can be used. Since metal plates are prone to corrosion in PEMFC systems, efforts have been made to prevent corrosion.

[0027] Furthermore, in the PEMFC 10, the BPP 20 also presents another material challenge, as the BPP 20 also needs to be conductive to facilitate electron transfer for the oxygen reduction reaction. Therefore, the BPP 20 material needs to be conductive but chemically inert to react with ions present in the PEMFC 10 environment.

[0028] Typically, the BPP metal surface contains a coating such as a graphite-like coating or a protective oxide or nitride coating to increase the corrosion resistance of the BPP 20. The BPP 20 surface may therefore contain elements such as Fe, Cr, Ni, Mo, Mn, Si, P, C, S, F, or combinations thereof. Alternative coatings include Ti alloys, doped TiO x , Cr2O3, TiO2, TiN, CrN or ZrN. However, in an aggressive corrosive environment such as in a PEMFC 10, where the coating is more likely to degrade faster, there is still a need for a coating or material that is economically viable, corrosion resistant, protective against acids such as HF at the PEMFC operating temperature of about 80°C, electronically conductive and capable of simultaneously forming a coherent interface (i.e., a small interfacial contact resistance) with a metal substrate.

[0029] The metal phosphide materials disclosed herein solve one or more of the above problems and / or provide the benefits described herein. 3- Phosphides have various structural and performance characteristics. Phosphides can be binary single phosphides such as aluminum phosphide, zinc phosphide, calcium phosphide. Phosphides can be polyphosphides containing P-P bonds. Some polyphosphides have P2 4- ions, others may contain P 11 3- Although phosphorus has common oxidation states of 3-, 3+, or 5+, it may have oxidation states of 2-, 1-, 0, 1+, 2+, 4+ in addition to its common oxidation states, especially when chemically forming metal phosphides.

[0030] It has surprisingly been discovered that the phosphide materials disclosed herein provide corrosion resistant, electrically conductive properties to substrates such as BPP metal substrates.

[0031] A non-limiting example of BPP 20 is shown in Figure 2 . BPP 20 represents a non-limiting example of a substrate having a solid body or body portion 22 and a surface portion 24. The body portion 22 may be formed of a metal such as steel, stainless steel, aluminum, copper, alloys of two or more metals, or the like, or a combination thereof. Alternatively, the body portion 22 may be formed of a composite material such as a carbon-carbon composite, a carbon-polymer composite. Still alternatively, the body portion 22 may be made of graphite.

[0032] The surface portion 24 comprises a corrosion resistant, chemically inert, electrically conductive, and thermodynamically stable material disclosed herein. The entire area of ​​the surface portion 24 may comprise the material. Alternatively, the surface portion 24 may comprise one or more sub-portions without the material. In an example embodiment, the entire surface portion 24 may comprise the material so that the entire BPP 20 is protected from corrosion. In other applications, such as non-BPP applications, only a small portion of the surface portion 24 may comprise the material, such as less than about ½, ¼, 1 / 8, 1 / 16, 1 / 32, etc. of the surface portion may comprise the material.

[0033] The surface portion 24 may include one or more layers of the disclosed phosphide material. The material thickness on the surface portion 24 may be adjusted according to the needs of a particular application. Non-limiting examples of the material layer thickness may be about 0.1-0.8 μm, 0.2-0.6 μm, or 0.3-0.5 μm. Alternatively, the material may be layered to form a relatively thick deposit on the surface portion 24 having a size greater than 1 μm, such as about or at least about 1.25, 1.5, 1.75, 2.0, 2.25, 2.5, 2.75, 3.0, 3.25, 3.5, 3.75, 4.0, 4.25, 4.5, 4.75, 5.0, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 200, 250 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 200, 250, 300, 350, 400, 450, or 500 nm. The material can form one or more layers or multiple layers on the body portion 22. The material can form 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or more layers on the body portion 22. Relative to the thickness of the surface portion 24, each layer may have a thickness within the nanometer or micrometer range described herein.

[0034] The disclosed phosphide materials are characterized by at least the following properties: (1) thermodynamic stability, (2) electrical conductivity, and (3) chemical inertness. Thermodynamic stability ensures that the material does not readily decompose into other stable phase mixtures. Thermodynamic stability can be defined as whether the coating material is on a convex-hull in the chemical space of the elements that make up the material. Thermodynamic stability also relates to the ability or synthetic ability to successfully produce a stable material. In order to ensure that the material candidates can be experimentally obtained, only compounds with an absolute "zero" convex-hull distance are considered for the purposes of this disclosure.

[0035] Regarding the second criterion, the conductivity can be determined by the band gap (E g ) (also called energy gap). The band gap refers to the energy difference between the top of the valence band and the bottom of the conduction band. Materials with large band gaps are generally insulators, while those with smaller band gaps are called semiconductors. Conductors either have no band gap (i.e., metallic) or have a very small band gap (i.e., semi-metallic). The materials disclosed herein include metals (i.e., zero band gap) and other metallic materials with relatively small band gaps (<1 eV). Material candidates that do not have a "zero" band gap can be used as BPP surface materials as long as the material is designed to be thin enough to remain conductive (i.e., thin enough so that electrons can pass through the thickness of the material) and / or can be doped with other elements to increase conductivity.

[0036] Chemical inertness involves the material's ability to react with compounds present in the fuel cell environment, such as H3O + , HF and SO3 - For example, when the material is reacted with a dilute amount (δ) of HF, the material can decompose into a phase mixture that is more stable in chemical space. It is believed that the HF in the fuel cell environment + , HF, SO3 - 94, 95, 96, 97, 98, 99, or more of the starting material in the presence of H3O + , HF and SO3 - After contact and reaction, they remain on the product side together with the decomposition species. Some metal and semimetal phosphides may react with species such as H3O + HF is protective, but it is not effective for SO3 - Not completely protective.

[0037] The material may include a binary phosphide. The binary phosphide may be a metal or semi-metal phosphide. The material may have the following general formula (I):

[0038] A x P y (I)

[0039] in

[0040] A is an alkali metal, alkaline earth metal, transition metal, post-transition metal or metalloid, and

[0041] x and y are each a number independently selected from 1-15.

[0042] A can be an element of Group I.A, II.A, III.A, IV.A, I.B, II.B, III.B, IV.B, VB, VI.B, VII.B, VIII.B and / or the second, third, fourth, fifth or sixth period of the periodic table. A can be an alkali metal such as Li, Na, K, Rb, Cs, an alkaline earth metal such as Mg, Ca, Sr, Ba, a transition metal such as Sc, Y, Ti, Zr, V, Nb, Cr, Mo, Mn, Fe, Co, Ni, Cu, Zn, a post-transition metal including Al, Ga, Sn, or a metalloid such as Si. A is solid and not liquid or gas. A is not phosphorus.

[0043] x, y can be any number from 1 to 15, including fractions such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. 1 ≤ x, y ≤ 15. x = y, x < y, or x > y.

[0044] Alternatively, the material may comprise a ternary phosphide. The ternary phosphide may be a metal or semi-metal phosphide. The material may have the following general formula (II):

[0045] A x B z P y (II),

[0046] in

[0047] A and B are each one of an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal or a metalloid, and

[0048] x, y, z are each a number independently selected from 1-15.

[0049] A, B can each be an element from the same or different I.A, II.A, III.A, IV.A, IB, II.B, III.B, IV.B, V.B, VI.B, VII.B, VIII.B and / or the second, third, fourth, fifth or sixth period of the periodic table. A and B can be different elements. A, B can each be an alkali metal such as Li, Na, K, Rb, Cs, an alkaline earth metal such as Mg, Ca, Sr, Ba, a transition metal such as Sc, Y, Ti, Zr, V, Nb, Cr, Mo, Mn, Fe, Co, Ni, Cu, Zn, a post-transition metal including Al, Ga, Sn, or a metalloid such as Si. A, B are solid and not liquid or gas. A, B are not phosphorus.

[0050] x, y, z can each be any number from 1 to 15, including fractions such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. 1 ≤ x, y, z ≤ 15. y ≥ x + z, x ≥ y + z, z ≥ x + y, x = z = y, y ≤ x +z, x ≤ y + z, z ≤ x + y, y ≥ x or z, x ≥ y or z, z ≥ x or y, y ≤ x or z, x ≤ y or z, or z ≤ x or y.

[0051] In at least some embodiments, the surface portion may comprise at least one binary and at least one ternary phosphide. The material may comprise a mixture of binary and ternary phosphides. The material may comprise more binary phosphides than ternary phosphides, or vice versa.

[0052] Example

[0053] In order to evaluate which phosphide materials meet all three performance requirements listed above, high throughput (HT) first principles density functional theory (DFT) was used to calculate the results. The open materials databases materialsproject.org (MP) and OQMD.org (OQMD) were used to screen the best metal phosphide materials / coatings for BPP. Although it has been well established in the literature that metastable materials with convex hull distances less than 25 meV / atom can be experimentally obtained, only compounds with absolute "zero" convex hull distances (in both MP and OQMD) were considered to ensure that the material candidates can be experimentally obtained with confidence. Regarding the second direction, the research focused on conductive materials including metals (i.e., zero band gap) and other metal phosphides with relatively small band gaps (<1 eV). Regarding the third direction, the lowest energy pathways in the thermodynamic database were used to determine the specific reaction pathways of the materials.

[0054] For example, when titanium phosphide reacts with a dilute amount (δ) of HF, it can decompose into a mixture of phases that are more stable in chemical space. The specific reaction pathway can be determined using the lowest energy pathway within the thermodynamic database: TiP2 + δ HF→ x TiP2+ y TiF3+ z P + w H (where x, y, z, and w vary depending on δ and the relative ground state phase composition). Use δ = 0.1 to determine the appropriate phosphide material. In addition, evaluate the reaction enthalpy corresponding to each reaction ( ΔH 反应 , in eV / atom) and determines the amount of material remaining after the reaction has occurred.

[0055] The following Tables 1-3 list metal and semi-metal phosphide materials that are feasible as conductive and corrosion resistant materials for use as BPP surface materials. In Tables 1-3, the following abbreviations are used in the remarks section:

[0056] mb – medium bandgap (0 < E g < 1 eV);

[0057] hb – high bandgap (>1 eV);

[0058] d H3O – in with H3O + Decomposes during reaction so that > ​​20% of the material is converted into other phase mixtures;

[0059] d HF - decomposes upon reaction with HF such that >20% of the material is converted to other phase mixtures; and

[0060] d SO3 – in combination with SO3 - The reaction decomposes so that >20% of the material is converted into other phase mixtures.

[0061] Examples 1-28

[0062] Table 1 - Non-limiting Examples 1-28 of Metal Phosphides and Their Properties

[0063] .

[0064] As can be seen from Table 1, the metal phosphides of Examples 1-28 listed above have the desired three properties of thermodynamic stability, electrical conductivity, and chemical inertness to corrosive species of the fuel cell. The phosphides may optionally be doped with N, C, F, and / or other elements to further enhance electronic conductivity. Doping may be particularly beneficial for Examples 4, 6-8, 14-19, and 28 because these phosphide species have semiconductor properties.

[0065] All phosphide species of Examples 1-28 tested above are thermodynamically stable and have + , HF and SO3 - All of these species also have relatively small band gaps (<1 eV), with most of these species having a band gap of 0 eV. For all species in Table 1, + , HF and SO3 - Over 80 mol % of the material will not decompose upon reaction. Therefore, the metal phosphides identified in Table 1 are expected to be stable metallic or semi-metallic materials that can withstand the corrosive environment of a fuel cell as a BPP surface material.

[0066] The metal phosphides described in Table 1 may form a surface portion of the BPP. The surface portion may be up to several µm thick. Non-limiting examples of the thickness of the material layer may be about 0.1 nm-250 µm, 1 nm-200 µm, or 10 nm-100 µm. Alternatively, the surface portion may be about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 5.0, 10, 115, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 200, 250 µm thick. Examples 1-28 of Table 1 may also be applied at the nanoscale, such that the thickness of the surface portion comprising one or more metal and semi-metal phosphides of Table 1 may be about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3. 400, 420, 450, 480, 500, 520, 550, 580, 600, 650, 700, 750, or 800 nm thick.

[0067] Examples 29-47

[0068] Table 2 - Non-limiting examples 29-47 of metal or semi-metal phosphides and their properties

[0069]

[0070] .

[0071] As can be seen from Table 2, the semi-metal phosphides of Examples 29-47 identified in Table 2 are expected to be stable and therefore can be synthesized and are protective against the corrosive environment of fuel cells, but the materials are either (1) insulating, such that the band gap is above 1 eV, but are resistant to the corrosive species H3O + , HF and SO3 - Protective, either (2) conductive, but to SO3 - No protective properties. More specifically, the following species belong to category (1): Ca5P8 ( C2 / m ) - Example 31, BaP 10 ( Cmc2 1 ) - Example 44 and Ba3P 14 ( P2 1 / c ) – Example 45. The remaining phosphides in Table 2 belong to category (2), which - After the reaction, only 41 mol % to 79 mol % of the initial phosphide material remains.

[0072] Like the phosphide species in Table 1, the phosphides of Examples 29-47 may optionally be doped with N, C, F and / or other elements to further enhance electronic conductivity. Doping may be particularly beneficial for Examples 29-31, 40 and 43-47 because these example phosphide species have semiconductor properties.

[0073] Based on these results, it is expected that the semi-metallic phosphides of Examples 29-47 should be applied as a thinner surface layer at the nanometer scale to obtain the desired target conductivity compared to the metal phosphides of Examples 1-28 of Table 1. Non-limiting examples of the thickness of the material layer can be about 0.01 nm-150 μm, 0.1 nm-100 μm, or 1 nm-50 μm. The surface portion / layer using one or more embodiments 29-47 can be about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4. 9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 5.0, 7.0, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 420, 450, 480, 500 nm thick. Alternatively, the surface portion can be about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2. 3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 5.0, 10, 115, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 µm thick.

[0074] Examples 48-69

[0075] Table 3 - Non-limiting examples 48-69 of metal or semi-metal phosphides and their properties

[0076]

[0077] .

[0078] As shown in Table 3, the phosphide species of Examples 48-69 have generally poor protection against the respective corrosive species of the fuel cell environment compared to Examples 1-47. Although all Examples 48-69 are thermodynamically stable and therefore synthesizable, they are either insulating or have no protection against at least one of the corrosive species. Examples 48-69 can be used as a surface layer of a BPP in the form of a relatively thin layer / coating.

[0079] The surface portion comprising one or more embodiments 48-69 can be about or at least about 0.01 nm-150 μm, 0.1 nm-100 μm, or 1 nm-50 μm. The surface portion using one or more embodiments 29-47 can be about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 5.0, 7.0, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 420, 450, 480, 500 nm thick. Alternatively, the surface portion can be about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2. 3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 5.0, 10, 115, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 µm thick.

[0080] The phosphides of Examples 48-69 may optionally be doped with N, C, F and / or other element(s) to further enhance electronic conductivity. For Examples 48-52, 64 and 65, doping may be particularly beneficial because of these example phosphide species.

[0081] The phosphides of Table 3 may initially be less protective, but can consume or scavenge acidic species in the PEMFC environment, thereby protecting the bulk of the BPP.

[0082] Alternatively, all of the phosphides disclosed herein may be combined with other materials having protective properties, such as metal oxides, nitrides, carbides, fluorides, or combinations thereof. The surface portion 24 may thus comprise one or more metal phosphates and at least one other material such as an oxide, carbide, nitride, fluoride, or the like. For example, the surface portion may comprise about or at least about 1-99, 10-90, 20-80, 30-70, 40-60, or 50 wt % or volume % of one or more phosphates disclosed herein and 1-99, 10-90, 20-80, 30-70, 40-60, or 50 wt % or volume % of at least one other material.

[0083] For example, the insulating but protective materials of Table 3 may be combined with a conductive material such as at least one conductive oxide, nitride, carbide, or a combination thereof.

[0084] The metal phosphides disclosed herein can further react with oxygen and / or water to form metal phosphates: M(PO4) x Such metal phosphates can remain on the BPP surface, or dissolve in the acidic electrolyte. The dissolved metal phosphates can become phosphoric acid, which can increase or decrease the pH of the electrolyte, depending on the PEMFC operating conditions. The metal phosphates reacting with oxygen and / or water can form a relatively thin passivation layer, which can prevent further reactions.

[0085] Under very oxidizing conditions, some phosphides can react to form gaseous species. They can help protect the BPP by consuming and scavenging acidic species that can cause further degradation of the PEMFC. Some decomposition species of metal phosphides may be conductive, which can help electron transport in the PEMFC. Metal phosphides and / or their decomposition species can form a stable, conductive and protective interfacial layer on the BPP.

[0086] The corrosion resistance of a BPP comprising a metal bulk portion and a surface portion comprising the disclosed metal phosphide(s) may be about or less than about 0.1-20, 0.5-15, or 1-10 µA cm at 80°C, pH = 2 to 3, and the presence of ~0.1 ppm HF in solution. -2Under the same operating conditions, the corrosion resistance may be less than about 2.5, 1.75, 1.5, 1.25, 1, 0.75, 0.5, 0.25, or 0.1 µA cm -2 .

[0087] The conductivity of the surface portion of the BPP comprising the disclosed metal phosphide(s) may be about or greater than about 0.1-150, 1-120, or 10-100 S cm -1 The thickness of the surface portion comprising the disclosed (one or more) metal phosphides can be optimized to achieve a target conductivity. The conductivity can be greater than about 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, or 150 S cm -1 .

[0088] The interfacial contact resistance between the BPP bulk portion and the surface portion comprising the disclosed metal phosphide(s) may be about or less than about 0.001-0.1, 0.005-0.08, or 0.01-0.05 ohm cm 2 The interfacial contact resistance may be less than about 0.05, 0.04, 0.03, 0.02, 0.01, 0.009, 0.008, 0.007, 0.006, 0.005, 0.004, 0.003, 0.002, 0.001 ohm cm 2 .

[0089] BPP has been described as a suitable application for the disclosed phosphide materials, but the materials may be suitable for other applications as well. For example, the disclosed phosphide materials may be used as part of a surface portion of other industrial applications requiring a chemically inert conductive material, such as batteries, photovoltaic systems, consumer electronics, and / or anywhere else where a conductive and inert oxide would be beneficial. Thus, the application of the materials is not limited to metals, but any substrate requiring chemically inert and conductive properties. Thus, the substrate may be glass, ceramic, composite material, polymer, etc.

[0090] Additionally, various methods of synthesizing the corrosion resistant and electrically conductive phosphide materials are disclosed herein. In at least one embodiment, the method may include a solution-based process, an electrochemical method, a thermal treatment, or a combination thereof.

[0091] Example methods may include reacting a metal-containing and phosphorus-containing precursor chemical such as M(NO3) x 、M(OH) x 、MCl x, NH4HPO4, (NH4)2HPO4, etc. are dissolved in water or an organic solvent and then dispersed on the metal BPP at about 0-150, 20-120 or 40-100° C. with different aging times of about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60 or more minutes. The reaction time can also be varied and, for example, lasts for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 16, 24 or 48 hours. The pH of the solution can be controlled by the presence of oxidation / reduction chemicals. The phosphorus-containing precursor can be a metal phosphate (MPO4; for example, FePO4) or a metal phosphate hydrate (MPO4·xH2O), which can be reduced to a metal phosphide under reducing conditions.

[0092] Alternatively, the bulk region of the BPP, such as a stainless steel region, can be polished and cleaned with an organic solvent such as ethanol. The method can then include electrochemically depositing a metal phosphide from the precursor. The working electrode is typically a stainless steel plate, where the counter electrode and reference electrode can vary depending on the voltage window. Typically, Pt foil and / or Ag / AgCl (with saturated KCl) can be used as the counter electrode and reference electrode. The immersed electrolyte solution can be an acid with varying concentrations, such as sulfuric acid of about 0.01-1M. The exact pH can be adjusted or neutralized as needed.

[0093] The heat treatment method may include heat treating the BPP metal such as stainless steel and / or other metals with a metal phosphide precursor in a furnace at about 200-1500, 300-1200, or 400-1000° C. in the presence of a mild oxidant such as air or a reducing agent such as Ar, N 2 , or H 2 .

[0094] Alternatively, the bulk portion of BPP can be produced to contain a relatively large amount of phosphorus, such that the bulk portion is enriched in P and comprises about or at least about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1 .5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.25, 2.5, 2.75, 3.0, 3.25, 3.5, 3.75, 4.0, 4.25, 4.5, 4.75, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 volume or weight % or more of P, based on the total volume or weight of the BPP or the bulk portion. The method may further include providing a sufficient amount of one or more metals or semimetals designated as A, B in formulas (I) and (II) such that elements A and / or B, when reacting with the phosphorus of the bulk portion, form the phosphides disclosed herein.

[0095] Alternatively, the metal phosphide may be deposited onto the body portion via a solid state route, pulsed laser deposition (PLD), atomic layer deposition (ALD) and / or chemical vapor deposition (CVD) or the like.

[0096] Although exemplary embodiments are described above, it is not intended that these embodiments describe all possible forms included in the claims. The words used in the specification are descriptive words rather than restrictive, and it should be understood that various changes can be made without departing from the spirit and scope of the present disclosure. As previously mentioned, the features of the various embodiments can be combined to form other embodiments that may not be clearly described or shown. Although various embodiments may be described as providing advantages or being superior to other embodiments or prior art embodiments in terms of one or more required characteristics, it is recognized by those of ordinary skill in the art that one or more features or characteristics can be compromised to achieve the desired overall system properties, depending on the specific application and implementation. These properties may include, but are not limited to, cost, strength, durability, life cycle cost, marketability, appearance, packaging, size, applicability, weight, manufacturability, ease of assembly, etc. Therefore, for any embodiment described as being less desirable in terms of one or more features than other embodiments or prior art embodiments, these embodiments are not outside the scope of the present disclosure and may be desirable for specific applications.

Claims

1. A proton exchange membrane fuel cell bipolar plate, comprising: A metal substrate having a bulk portion and a surface portion, the surface portion comprising a corrosion resistant conductive binary phosphide material having formula (I): A x P y (I), in The binary phosphide material is configured to impart corrosion resistance and electrical conductivity to the metal substrate, Among them A x P y Selected from VP2,CrP4,MnP4,Fe3P,FeP2,FeP4,CoP3,NiP2,Ni3P,NiP3,Ni5P4,Ni 12 P5, Cu2P7, CuP2, Zn3P2, Rb2P3, Sr3P4, YP5, ZrP2, Zr7P4, Nb7P4, Mo3P, MoP2, MoP4, Sn4P3, SnP3 and Ba5P4.

2. The bipolar plate according to claim 1, wherein the corrosion resistance of the bipolar plate is less than 10 μAcm at 80°C, pH 2-3, and 0.1 ppm HF in the solution. -2 .

3. The bipolar plate according to claim 1, wherein A x P y Selected from NiP2, Ni3P, NiP3, Ni5P4 and Ni 12 P5.

4. The bipolar plate according to claim 1, wherein A x P y Selected from ZrP2 and Zr7P4.

5. The bipolar plate according to claim 1, wherein the conductivity of the binary phosphide material is greater than 100 S cm -1 .

6. The bipolar plate of claim 1, wherein the surface portion comprises at least 50 wt% of a dibasic phosphide.

7. The bipolar plate of claim 1, wherein the body portion is steel, graphite, aluminum, titanium, or copper. 8 . The bipolar plate of claim 1 , wherein the surface portion further comprises a dopant including at least one of N, C, or F.

9. A corrosion-resistant and electrically conductive substrate comprising: The body part; and A surface part material, the surface part material comprising a binary phosphide having the formula (I): A x P y (I), The surface material is configured to provide the substrate with a conductivity of less than 10 μA cm at 80° C., pH 2-3, and the presence of 0.1 ppm HF in the solution. -2 Corrosion resistance and greater than 100S cm -1 The conductivity of Among them A x P y Selected from VP2,CrP4,MnP4,Fe3P,FeP2,FeP4,CoP3,NiP2,Ni3P,NiP3,Ni5P4,Ni 12 P5, Cu2P7, CuP2, Zn3P2, Rb2P3, Sr3P4, YP5, ZrP2, Zr7P4, Nb7P4, Mo3P, MoP2, MoP4, Sn4P3, SnP3 and Ba5P4.

10. The substrate according to claim 9, wherein A x P y Selected from NiP2, Ni3P, NiP3, Ni5P4, Ni 12 P5, ZrP2 and Zr7P4. 11 . The substrate according to claim 9 , wherein the surface portion material further comprises a dopant, the dopant comprising at least one of N, C, or F.